2008
DOI: 10.1021/es702483d
|View full text |Cite
|
Sign up to set email alerts
|

Nitrification in Premise Plumbing: Role of Phosphate, pH and Pipe Corrosion

Abstract: Nitrification in PVC premise plumbing is a weak function of pH over the range 6.5-8.5 and is insensitive to phosphate concentrations 5-1000 ppb. Lead pipe enhanced nitrification relative to PVC, consistent with expectations that nitrifiers could benefit from ammonia recycled from nitrate via lead corrosion. Relatively new copper pipe (<1.5 years old) did not allow nitrifiers to establish, but nitrifiers gradually colonized over a period of months in brass pipes when copper concentrations were reduced by pH adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
60
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 17 publications
7
60
0
Order By: Relevance
“…In other studies, Rhodococcus, Stenotrophomonas, and Xanthomonas have been shown to decrease copper levels by sorbing soluble copper in their exopolysaccharide (EPS) (2,28,47). Nitrification may also promote corrosion, as this process results in a pH drop which increases the solubility of most lead minerals commonly found on the surfaces of lead materials in DWDSs (48,49).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…In other studies, Rhodococcus, Stenotrophomonas, and Xanthomonas have been shown to decrease copper levels by sorbing soluble copper in their exopolysaccharide (EPS) (2,28,47). Nitrification may also promote corrosion, as this process results in a pH drop which increases the solubility of most lead minerals commonly found on the surfaces of lead materials in DWDSs (48,49).…”
mentioning
confidence: 98%
“…Biofilms have been shown to influence the corrosion behavior of metals, including those used in drinking water pipes (6,7,9,11,48). For example, drinking water isolates of the genera Agrobacterium, Acidovorax, Sphingomonas, and Micrococcus have been reported to increase copper levels in drinking water pipes, with corrosion dependent on microbial activity (9,10,14,23,37).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When excessive levels of free ammonia are present in the source water or ammonia is added to form chloramines, nitrification may occur with sufficient dissolved oxygen (DO) (34). Nitrification in the DS, and the pH drop associated with nitrification, can impact the corrosion rates of the DS and premise materials (41). In addition, the increased chlorine demand and growth of heterotrophic biofilms produce undesirable taste and odor issues (30).…”
mentioning
confidence: 99%
“…So, the copper plumbing material is widely used. This may be due to the easy fittings with different pipe varieties [55,56]. Metal-based materials can form the corrosion products on pipe surfaces and release metals into water as a result of chemical or biological reactions [57,58].…”
Section: Discussionmentioning
confidence: 99%